2022
DOI: 10.1175/jpo-d-21-0122.1
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and Dispersion of Global Eddy Propagation from Satellite Altimetry

Abstract: It is well understood that isolated eddies are presumed to propagate westward intrinsically at the speed of the annual baroclinic Rossby wave. This classic description, however, is known to be frequently violated in both propagation speed and its direction in the real ocean. Here, we present a systematic analysis on the divergence of eddy propagation direction (i.e., global pattern of departure from due west) and dispersion of eddy propagation speed (i.e., zonal pattern of departure from Rossby wave phase spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…According to previous conclusions, westward-propagating eddy velocities can be increased by westward mean flows or reversed in strong eastward mean currents (e.g., Chen et al, 2022;Klocker & Abernathey, 2014). In contrast, a surface-intensified eastward mean flow can increase the westward long Rossby wave speed, but a surface westward flow is ineffective (e.g., Colin de Verdière & Tailleux, 2005;Liu, 1999).…”
Section: Eddymentioning
confidence: 91%
“…According to previous conclusions, westward-propagating eddy velocities can be increased by westward mean flows or reversed in strong eastward mean currents (e.g., Chen et al, 2022;Klocker & Abernathey, 2014). In contrast, a surface-intensified eastward mean flow can increase the westward long Rossby wave speed, but a surface westward flow is ineffective (e.g., Colin de Verdière & Tailleux, 2005;Liu, 1999).…”
Section: Eddymentioning
confidence: 91%
“…A more remarkable fact is that Chen et al. (2022) indicate that the global eddy propagation is distributed in all directions rather than a single westward or eastward. For the clustering of eddy trajectories with large variations in the spatial propagation direction, it seems necessary to consider their spatial direction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Peng et al (2022) found that the magnitude of change in current and wind field stress simultaneously affected the zonal propagation of eddies. Chen et al (2022) believed that the effect of wind fields on eddy motion is indirect. On the other hand, Fu (2009) pointed out that the mean propagation of the eddy generally follows the fronts (e.g., the Subtropical Front, the Sub-Antarctic Front, and the Polar Front) due to being steered by the topography feature in the Southern Ocean.…”
mentioning
confidence: 99%
See 2 more Smart Citations